Perceptions of Accounting Professionals on IFRS Application at the Individual Financial Statements: Evidence from Romania - Marian Sacarin; Stefan Bunea; Maria Madalina Girbina (Journal of Accounting and Management Information Systems (JAMIS), 2013)
For the accounting year 2012 companies whose securities are listed on Bucharest Stock Exchange are required to present their individual financial statements in conformity with IFRS by restating the information prepared in compliance with national regulations. Moreover, starting 1st January 2013, these companies are applying IFRS as the basis of accounting. A peculiarity of this transition process is that listed entities were not required to present two sets of accounts before switching to IFRS (as it was the case for financial institutions). As we considered that the attitude of main stakeholders involved in the process is a precondition for high quality IFRS financial statements, the objective of our study was to illustrate the opinion of accounting professionals on this decision. The study surveys 142 accounting professionals who, throughout years 2012 and 2013, have attended the continuing training courses organized by the Body of Expert and Licensed Accountants of Romania. We identified that respondents are aware of the benefits of IFRS application, 79.6% of indicating that the companies listed on the BSE should have applied IFRS to the preparation of individual financial statements, even if they had not been required to do so. However, 69.7% of them believed that the application of IFRS should have been concurrent, in an initial stage, with the application of national regulations before proceeding with the application of IFRS as the basis of accounting. Furthermore, they perceive the fiscal risk as the greatest difficulty in the transition to IFRS. The most important benefit is the increased attractiveness to investors, while adapting the IT systems is considered the most significant cost. Overall, 63% of the respondents have indicated that the benefits of applying IFRS outweigh the costs.
Keywords: M41; M48; N20; G18; 650; Accounting professionals; International Financial Reporting Standards (IFRS); Individual financial statements; Listed companies; Bucharest Stock Exchange (BSE)